A method for producing reinforced ultrafine hard metal

CN122918374APending Publication Date: 2026-10-16SHAANXI AERONAUTIC CARBIDE TOOL CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611026463.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,现有技术中引入的强化相往往存在以下问题:强化相与基体之间的热膨胀系数差异较大,烧结冷却过程中产生热应力,导致合金内部微裂纹萌生;强化相在高温烧结条件下发生分解或过度固溶,丧失其强化特性;强化相分布不均匀,局部团聚形成缺陷源,反而降低合金性能

Benefits of technology

[0014] The beneficial effects of the technical solutions provided in the embodiments of the present invention include at least the following:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918374A_ABST
    Figure CN122918374A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of reinforced ultrafine hard alloy and belongs to the technical field of powder metallurgy. After ruthenium powder and ultrafine tungsten carbide powder are mixed by ball milling, a ruthenium tungsten carbide compound is synthesized by solid phase reaction in a vacuum sintering furnace, and the ruthenium tungsten carbide compound is broken by dry grinding and used as a dispersion strengthening phase. The ruthenium tungsten carbide compound powder, tungsten carbide powder, cobalt powder, chromium carbide and carbon black are mixed according to specific mass ratios, wet grinding is carried out under low-temperature cooling conditions, and the reinforced ultrafine hard alloy is prepared after spray drying, pressing forming, dewaxing and vacuum sintering. The method realizes the uniform dispersion distribution of the ruthenium tungsten carbide compound in the ultrafine tungsten carbide matrix by pre-synthesizing the strengthening phase and controlling the wet grinding temperature, and the carbon content of the alloy is accurately controlled by using carbon black, so that the formation of an eta phase is avoided. The obtained alloy tungsten carbide grains have high hardness, high bending strength and high fracture toughness, and are suitable for the cutting machining of carbon fiber reinforced composite materials, nickel-based high-temperature alloys and hardening steels and other difficult-to-machine materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of powder metallurgy technology, and in particular to a method for preparing reinforced ultrafine cemented carbide. Background Technology

[0002] Ultrafine cemented carbide refers to cemented carbide materials with tungsten carbide grain sizes in the submicron range. Due to its combination of high hardness and high toughness, it is widely used in the machining of difficult-to-machine materials such as carbon fiber reinforced composites, nickel-based superalloys, and hardened steel. In ultrafine cemented carbide, the small tungsten carbide grain size and significantly increased grain boundary area lead to a grain boundary strengthening effect that increases the alloy's hardness. However, the increased number of grain boundaries also provides more channels for crack propagation, resulting in a decrease in alloy toughness. Therefore, how to improve alloy toughness while maintaining an ultrafine grain size is the core problem facing ultrafine cemented carbide preparation technology.

[0003] Traditional methods for preparing ultrafine cemented carbides primarily control alloy properties by optimizing tungsten carbide powder particle size, cobalt powder content, and sintering process parameters. However, due to the inherent characteristics of the tungsten carbide-cobalt binary system, the contradiction between alloy hardness and toughness remains difficult to fundamentally resolve. To overcome this bottleneck, researchers have attempted to introduce reinforcing phases such as rare earth elements, carbide grain growth inhibitors, or intermetallic compounds into the alloy to improve its overall performance through mechanisms like dispersion strengthening and grain boundary strengthening. However, the reinforcing phases introduced in existing technologies often suffer from the following problems: a significant difference in thermal expansion coefficients between the reinforcing phase and the matrix, leading to thermal stress during sintering and cooling, resulting in the initiation of microcracks within the alloy; decomposition or excessive solidification of the reinforcing phase under high-temperature sintering conditions, resulting in the loss of its strengthening properties; and uneven distribution of the reinforcing phase, with local agglomeration forming defect sources, which actually reduces alloy performance.

[0004] Ruthenium, a platinum group metal, possesses a high melting point, high hardness, and excellent chemical stability. Introducing ruthenium into cemented carbide systems holds promise for achieving dispersion strengthening through the formation of high-hardness intermetallic compounds. However, direct mixing of ruthenium powder and tungsten carbide powder faces the following technical obstacles: ruthenium powder has a large particle size, significantly different from ultrafine tungsten carbide powder, making uniform dispersion difficult with simple mixing; ruthenium and tungsten carbide exhibit insufficient reactivity at conventional sintering temperatures, hindering the formation of an effective strengthening phase; and the synthesis conditions for ruthenium-tungsten carbide compounds are demanding, with improper control of parameters such as reaction temperature, holding time, and vacuum level easily leading to incomplete reactions or product decomposition.

[0005] Furthermore, in the preparation of ultrafine cemented carbide, process steps such as wet milling temperature control, precise carbon content regulation, and sintering densification have a significant impact on the final alloy properties. During wet milling, the slurry temperature inside the ball mill rises, causing cold welding and agglomeration of powder particles, affecting the uniformity of the mixture. When the alloy carbon content deviates from the stoichiometric ratio, it is easy to form brittle eta phase or free carbon, which deteriorates the alloy properties. During sintering, the flow of liquid cobalt and the growth behavior of tungsten carbide grains compete with each other, and improper selection of process parameters will lead to abnormal grain growth or residual porosity. Summary of the Invention

[0006] In summary, existing ultrafine cemented carbide preparation technologies are still insufficient to achieve a synergistic improvement in hardness and toughness by introducing a dispersed reinforcing phase while maintaining ultrafine grains. There is an urgent need for an ultrafine cemented carbide preparation method that can synthesize a stable reinforcing phase, achieve uniform dispersion, precisely control carbon content, and optimize the sintering process.

[0007] On the one hand, a method for preparing reinforced ultrafine cemented carbide is provided, comprising the following steps:

[0008] Ruthenium powder and ultrafine tungsten carbide powder are loaded into a ball mill, and cemented carbide grinding balls are added. The mass ratio of the balls to the powder is 2:1 to 3:1. The mixture is ball-milled at a speed of 80 to 120 rpm for 2 to 5 hours to obtain a mixed powder.

[0009] The mixed powder is placed in a graphite boat and then placed in a vacuum sintering furnace. The furnace is evacuated to a vacuum level not exceeding 10 Pa, and the temperature is increased at a rate of 3 to 5 degrees Celsius per minute to 1380 to 1480 degrees Celsius. The temperature is maintained for 1 to 3 hours, during which the ruthenium powder and tungsten carbide powder undergo a solid-phase reaction to produce a product with the chemical formula […]. Ruthenium tungsten carbide compounds are cooled to below 80 degrees Celsius to obtain bulk solids;

[0010] The solid blocks are loaded into a ball mill, and cemented carbide grinding balls are added. The ball-to-material mass ratio is 2:1 to 3:1. The mixture is dry-milled for 2 to 4 hours and then passed through a 60-mesh to 100-mesh sieve. The material passing through the sieve is ruthenium tungsten carbide compound powder.

[0011] By mass percentage, 0.5 to 2 parts of ruthenium tungsten carbide compound powder, 86 to 91 parts of tungsten carbide powder, 8 to 12 parts of cobalt powder, and 0.3 to 0.6 parts of chromium carbide are mixed, and anhydrous ethanol is added for wet milling. The amount of anhydrous ethanol added is 25% to 35% of the total mass of the mixture. The wet milling is carried out in an inclined ball mill, and the grinding balls are cemented carbide balls with a ball-to-material mass ratio of 4:1 to 6:1. The wet milling time is 28 to 40 hours. During the wet milling process, the temperature is controlled not to exceed 10 degrees Celsius by cooling water to obtain a mixed slurry.

[0012] The mixed slurry is spray-dried and pressed into shape, and then sintered at 1380°C to 1450°C for 1 to 2 hours under a vacuum of no more than 1 Pa to obtain a reinforced ultrafine cemented carbide.

[0013] Beneficial effects

[0014] The beneficial effects of the technical solutions provided in the embodiments of the present invention include at least the following:

[0015] Ruthenium powder and ultrafine tungsten carbide powder were ball-milled under specific ball-to-powder ratios and rotation speeds to coat the ruthenium powder particles with ultrafine tungsten carbide powder, forming a composite powder. The contact area between ruthenium and tungsten carbide in this composite powder is an order of magnitude larger than that of simple mixing, significantly improving the solid-state reaction efficiency. In a vacuum sintering furnace, under specific heating rates and holding times, ruthenium and tungsten carbide underwent a solid-state reaction to form ruthenium-tungsten carbide compounds. X-ray diffraction confirmed the disappearance of the characteristic diffraction peaks of ruthenium and the appearance of the characteristic diffraction peaks of the ruthenium-tungsten carbide compounds, proving the complete reaction. This synthesis method avoids the problem of uneven mixing caused by differences in particle size between ruthenium and tungsten carbide, providing a uniformly dispersed reinforcing phase raw material for subsequent alloy preparation.

[0016] The synthesized ruthenium tungsten carbide compound powder was dry-milled, crushed, and sieved before being wet-milled with tungsten carbide powder, cobalt powder, and chromium carbide. Because the particle size of the ruthenium tungsten carbide compound powder is in the micrometer range, the particle size difference with the ultrafine tungsten carbide powder is significantly reduced compared to the original ruthenium powder, resulting in a substantial improvement in the uniformity of the reinforcing phase dispersion in the matrix during wet milling. After sintering, the ruthenium tungsten carbide compound particles exist as a dispersed phase at the grain boundaries of the tungsten carbide grains, with the average particle size and interparticle spacing within a reasonable range, forming an effective dispersed reinforcing network.

[0017] During wet grinding, cooling water is introduced to control the slurry temperature to a specific value, preventing cold welding and agglomeration of powder particles due to temperature rise. This ensures the uniformity of the mixture and the uniform growth of tungsten carbide grains during subsequent sintering. Simultaneously, chromium carbide, acting as a grain growth inhibitor, effectively suppresses abnormal tungsten carbide grain growth during sintering, allowing the average grain size of tungsten carbide in the alloy to fully exert its fine-grain strengthening effect. Attached Figure Description

[0018] Figure 1 A flowchart provided for an embodiment of this application. Detailed Implementation

[0019] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0020] like Figure 1 As shown, a method for preparing a reinforced ultrafine cemented carbide includes the following steps:

[0021] Ruthenium powder and ultrafine tungsten carbide powder are loaded into a ball mill, and cemented carbide grinding balls are added. The mass ratio of the balls to the powder is 2:1 to 3:1. The mixture is ball-milled at a speed of 80 to 120 rpm for 2 to 5 hours to obtain a mixed powder.

[0022] The mixed powder is placed in a graphite boat and then placed in a vacuum sintering furnace. The furnace is evacuated to a vacuum level not exceeding 10 Pa, and the temperature is increased at a rate of 3 to 5 degrees Celsius per minute to 1380 to 1480 degrees Celsius. The temperature is maintained for 1 to 3 hours, during which the ruthenium powder and tungsten carbide powder undergo a solid-phase reaction to produce a product with the chemical formula […]. Ruthenium tungsten carbide compounds are cooled to below 80 degrees Celsius to obtain bulk solids;

[0023] The solid blocks are loaded into a ball mill, and cemented carbide grinding balls are added. The ball-to-material mass ratio is 2:1 to 3:1. The mixture is dry-milled for 2 to 4 hours and then passed through a 60-mesh to 100-mesh sieve. The material passing through the sieve is ruthenium tungsten carbide compound powder.

[0024] By mass percentage, 0.5 to 2 parts of ruthenium tungsten carbide compound powder, 86 to 91 parts of tungsten carbide powder, 8 to 12 parts of cobalt powder, and 0.3 to 0.6 parts of chromium carbide are mixed, and anhydrous ethanol is added for wet milling. The amount of anhydrous ethanol added is 25% to 35% of the total mass of the mixture. The wet milling is carried out in an inclined ball mill, and the grinding balls are cemented carbide balls with a ball-to-material mass ratio of 4:1 to 6:1. The wet milling time is 28 to 40 hours. During the wet milling process, the temperature is controlled not to exceed 10 degrees Celsius by cooling water to obtain a mixed slurry.

[0025] The mixed slurry is spray-dried and pressed into shape, and then sintered at 1380°C to 1450°C for 1 to 2 hours under a vacuum of no more than 1 Pa to obtain a reinforced ultrafine cemented carbide.

[0026] As an optional embodiment, the specific process of ball milling and mixing in step 1 is as follows:

[0027] Ruthenium powder with an average FSSS particle size of 15 to 35 micrometers and ultrafine tungsten carbide powder with an average FSSS particle size of 0.5 to 0.8 micrometers were loaded into a 5-liter horizontal ball mill. The mass ratio of ruthenium powder to ultrafine tungsten carbide powder was 1:0.8 to 2. Carbide grinding balls were added, with a mass of 2 to 3 times the total mass of ruthenium powder and ultrafine tungsten carbide powder. The mixture was ball-milled at a speed of 90 to 110 rpm for 3 to 4 hours.

[0028] During ball milling, larger ruthenium powder particles roll and adhere to the surface of smaller ultrafine tungsten carbide powder particles, forming a composite powder in which ruthenium powder is coated with ultrafine tungsten carbide powder. The contact area between ruthenium powder and ultrafine tungsten carbide powder in this composite powder is 10 times larger than that in simple mixing.

[0029] After ball milling, all the powder inside the ball mill is discharged, and the grinding balls and the material on the sieve are removed by passing the powder through a 40-mesh sieve. The material that passes through the sieve is the mixed powder.

[0030] As an optional embodiment, the specific process of vacuum carbonization in step 2 is as follows:

[0031] The mixed powder is loaded into a graphite boat with a filling height of 30 mm to 50 mm. The graphite boat is placed in the constant temperature zone of the vacuum sintering furnace. After closing the furnace door, the vacuum system is started and the vacuum is evacuated to below 5 Pa.

[0032] The temperature was increased from room temperature to 1400 to 1480 degrees Celsius at a rate of 4 to 5 degrees Celsius per minute, while the vacuum level was maintained below 10 Pa during the heating process.

[0033] After reaching the set temperature, maintain the temperature for 2 to 3 hours, and keep the vacuum level below 5 Pa during the heat preservation process;

[0034] After the heat preservation is completed, the heating power is turned off, and the furnace is cooled to below 80 degrees Celsius. Then the graphite boat is removed from the furnace to obtain a blocky solid.

[0035] X-ray diffraction was performed on the bulk solid sample. The scanning angle 2θ ranged from 20 to 90 degrees, the step size was 0.02 degrees, and the scanning speed was 2 degrees per minute. It was confirmed that the characteristic diffraction peaks of ruthenium at 2θ equal to 38.4 degrees, 44.0 degrees, and 64.6 degrees disappeared, and the characteristic diffraction peaks of ruthenium tungsten carbide compounds appeared at 2θ equal to 36.2 degrees, 42.5 degrees, and 61.8 degrees.

[0036] As an optional embodiment, the specific process of dry grinding and crushing in step 3 is as follows:

[0037] The solid blocks are loaded into a ball mill, and hard alloy grinding balls with a diameter of 5 mm to 10 mm are added. The ball-to-material mass ratio is 2.5:1 to 3:1. The balls are then dry-ground at a speed of 60 to 80 rpm for 3 to 4 hours.

[0038] The powder after dry grinding is passed through a 60-mesh sieve and an 80-mesh sieve in sequence. When passing through the 60-mesh sieve, the mass fraction of the material on the sieve is 5% to 10%, and it is returned to the ball mill for further dry grinding.

[0039] The material passing through the 60-mesh sieve is then passed through the 80-mesh sieve. When passing through the 80-mesh sieve, the mass fraction of the material on the sieve is 15% to 25%, and it is returned to the ball mill for further dry grinding.

[0040] The material passing through an 80-mesh sieve is ruthenium tungsten carbide compound powder, which has a particle size of 5 to 15 micrometers.

[0041] The ruthenium tungsten carbide compound powder is placed in a sealed container and stored under nitrogen protection for no more than 72 hours.

[0042] As an optional embodiment, the specific process of wet grinding of ingredients in step 4 is as follows:

[0043] By weight percentage, 0.8 to 1.5 parts of ruthenium tungsten carbide compound powder, 87 to 90 parts of tungsten carbide powder, 9 to 11 parts of cobalt powder, 0.4 to 0.6 parts of chromium carbide, and 0.04 to 0.06 parts of carbon black are loaded into an inclined ball mill.

[0044] Add anhydrous ethanol at a concentration of 28% to 32% of the total mass of the mixture, and then add polyethylene glycol (PEG) with a molecular weight of 4000 at a concentration of 1.2% to 1.8% of the total mass of the mixture.

[0045] Add carbide grinding balls with a diameter of 3 mm to 6 mm and a ball-to-material mass ratio of 5:1 to 6:1, and wet grind at an inclination angle of 15 degrees to 25 degrees and a rotation speed of 30 to 40 rpm for 32 to 36 hours.

[0046] During the wet grinding process, cooling water is introduced through the jacket of the ball mill. The inlet temperature of the cooling water is 5 to 8 degrees Celsius, and the outlet temperature does not exceed 12 degrees Celsius. The temperature of the slurry inside the ball mill is controlled to be no higher than 10 degrees Celsius.

[0047] After wet grinding, the slurry is discharged from the ball mill and passed through a 200-mesh sieve to remove the grinding balls. The material passing through the sieve is the mixed slurry.

[0048] As an optional embodiment, the carbon black is acetylene black, and the carbon black has a particle size of 30 nanometers to 50 nanometers and a specific surface area of ​​60 square meters per gram to 80 square meters per gram.

[0049] During the wet milling process, carbon black is uniformly dispersed in the mixed slurry. In the early stage of sintering, it reacts with excess oxygen in the mixed slurry to generate carbon monoxide, which then escapes.

[0050] Carbon black is used to supplement the carbon content in the alloy, so that the carbon content of the alloy reaches the stoichiometric ratio. After sintering, the free carbon content in the alloy is 0.04% to 0.08%, and there is no eta phase in the alloy.

[0051] As an optional embodiment, the specific process of spray drying and pressing in step 5 is as follows:

[0052] The mixed slurry is fed into a centrifugal spray dryer with an atomizing disc speed of 15,000 to 18,000 rpm, an inlet temperature of 200 to 220 degrees Celsius, an outlet temperature of 90 to 100 degrees Celsius, and a feed rate of 5 to 8 liters per hour.

[0053] The moisture content of the dried mixture is 0.1% to 0.3%, the Hall flowability is 30 seconds per 25 square centimeters to 45 seconds per 25 square centimeters, and the loose density is 2.8 g per cubic centimeter to 3.2 g per cubic centimeter.

[0054] The dried mixture is loaded into a mold and molded on a hydraulic press at a pressing pressure of 160MPa to 200MPa and a holding time of 3 to 5 seconds to obtain a pressed blank.

[0055] The density of the pressed blank is 52% to 55% of the theoretical density, and the dimensional accuracy of the pressed blank is ±0.5% of the nominal size.

[0056] As an optional embodiment, step 5, prior to sintering, further includes a dewaxing step:

[0057] The pressed blank is placed into a graphite boat in the sintering furnace, and the vacuum is drawn to below 1 Pa. The temperature is then increased from room temperature to 300 degrees Celsius at a rate of 1 to 3 degrees Celsius per minute.

[0058] Starting from 300 degrees Celsius, polyethylene glycol begins to decompose and volatilize. The temperature is then increased at a rate of 1 to 3 degrees Celsius per minute to 400 degrees Celsius, and held at 400 degrees Celsius for 0.5 to 1.5 hours.

[0059] Increase the temperature from 400 degrees Celsius to 600 degrees Celsius at a rate of 5 to 10 degrees Celsius per minute, and hold at 600 degrees Celsius for 10 to 20 minutes.

[0060] During the dewaxing process, the vacuum level inside the furnace is maintained below 1 Pa, and after the dewaxing is completed, the vacuum level returns to below 0.1 Pa.

[0061] The volatiles generated during dewaxing are collected by condensation and then treated uniformly.

[0062] As an optional embodiment, the specific process of sintering in step 5 is as follows:

[0063] The dewaxed compact is heated in a vacuum sintering furnace at a rate of 5 to 10 degrees Celsius per minute to 1400 to 1450 degrees Celsius per minute.

[0064] After reaching the set temperature, maintain the temperature for 1 to 2 hours, keeping the vacuum level below 0.1 Pa during the maintenance process;

[0065] During the sintering process, cobalt powder melts to form liquid cobalt, which flows along the gaps between tungsten carbide particles, filling the pores between the particles.

[0066] As an optional embodiment, the reinforced ultrafine cemented carbide has the following microstructure and property characteristics:

[0067] The average size of tungsten carbide grains is 0.5 to 0.8 micrometers. The cross-sectional length Lavg of no less than 500 grains is measured using the cross-sectional method. The average grain size d is calculated by the formula d = 1.56 multiplied by Lavg.

[0068] Ruthenium tungsten carbide compound particles exist as a dispersed phase at the grain boundaries of tungsten carbide grains, with an average particle size of 1 to 3 micrometers and a particle spacing of 1.5 to 3 micrometers.

[0069] The alloy has a Rockwell hardness (HRA) of 91.5 to 92.5, a bending strength of 3800 MPa to 4200 MPa, and a fracture toughness (KiC) of 9.5 MPa·m1 / 2 to 11.0 MPa·m1 / 2.

[0070] The reinforced ultrafine cemented carbide is used for machining carbon fiber reinforced composite materials, nickel-based superalloys, or hardened steel.

[0071] It should be noted that, regarding step 1, ball milling and mixing: the ruthenium powder particle size is 15 to 35 micrometers, and the ultrafine tungsten carbide powder particle size is 0.5 to 0.8 micrometers, representing a particle size difference of 20 to 70 times. During ball milling, the larger ruthenium powder particles roll on the surface of the smaller ultrafine tungsten carbide powder particles, causing the ruthenium powder particles to be coated by the ultrafine tungsten carbide powder, forming a core-shell structured composite powder. The contact area between the ruthenium powder and the ultrafine tungsten carbide powder in this composite powder is 10 times larger than that in simple mechanical mixing, providing a sufficient contact interface for subsequent solid-phase reactions.

[0072] Regarding step 2, vacuum carbonization: The graphite boat is filled to a height of 30 mm to 50 mm. This height ensures uniform heating of the mixed powder. Overfilling leads to incomplete reaction due to sluggish heat transfer within the powder, while underfilling reduces production efficiency. Vacuum is applied to below 5 Pa to remove oxygen from the furnace and prevent ruthenium powder oxidation. The heating rate is 3 to 5 degrees Celsius per minute. Excessive heating increases the temperature gradient within the boat and causes uneven reaction, while slow heating increases energy consumption. The holding temperature is 1380 to 1480 degrees Celsius for 1 to 3 hours. Below 1380 degrees Celsius, the solid-phase reaction rate is too low, resulting in incomplete reaction between Ru and WC, and residual elemental ruthenium in the product. Above 1480 degrees Celsius, Ru evaporation loss increases, causing the actual ruthenium content in the alloy to deviate from the design value.

[0073] about Compound: Ruthenium powder and tungsten carbide powder undergo a solid-state reaction at 1380°C to 1480°C. The reaction equation is as follows: Reaction products It has a cubic crystal structure with a lattice constant α equal to 0.402 nm. During X-ray diffraction, the characteristic diffraction peaks of elemental ruthenium are located at 2θ equal to 38.4°, 44.0°, and 64.6°. The characteristic diffraction peaks are located at 2θ equal to 36.2 degrees, 42.5 degrees, and 61.8 degrees. When the characteristic diffraction peaks of elemental ruthenium completely disappear and The appearance of characteristic diffraction peaks indicates that the solid-phase reaction has proceeded completely.

[0074] Regarding step 3, dry grinding: Dry grinding employs a two-step sieving process. The first step involves passing the material through a 60-mesh sieve. The oversize particles are coarse with a diameter greater than 250 micrometers, accounting for 5% to 10% of the total mass, and are returned to the ball mill for further grinding. The second step involves passing the material through an 80-mesh sieve. The oversize particles are medium-sized particles with a diameter of 180 to 250 micrometers, accounting for 15% to 25% of the total mass, and are also returned to the ball mill for further grinding. The undersize material from the 80-mesh sieve is ruthenium tungsten carbide compound powder, with a particle size of 5 to 15 micrometers. This powder is stored under nitrogen protection for no more than 72 hours. Storage beyond 72 hours will result in surface oxidation of the powder, leading to a decrease in subsequent sintering activity.

[0075] Regarding step 4, wet grinding: Wet grinding is carried out in a tilting ball mill with an inclination angle of 15 to 25 degrees. When the inclination angle is less than 15 degrees, the relative movement between the powder and the grinding balls is insufficient, resulting in low mixing efficiency. When the inclination angle is greater than 25 degrees, the powder accumulates at one end of the ball mill, leading to uneven mixing. The wet grinding time is 32 to 36 hours. Insufficient time results in uneven mixing of tungsten carbide and cobalt powder, leading to component segregation after sintering. Excessive time results in excessively fine tungsten carbide powder particles, increasing the sintering driving force and causing abnormal grain growth. During wet grinding, the temperature is controlled to not exceed 10 degrees Celsius using cooling water. Excessively high temperatures accelerate ethanol evaporation, increasing slurry viscosity and reducing grinding efficiency.

[0076] Regarding carbon black: The carbon black is acetylene black, with a particle size of 30 to 50 nanometers and a specific surface area of ​​60 to 80 square meters per gram. During wet milling, the carbon black is uniformly dispersed in the slurry mixture. In the early stages of sintering, when the temperature rises to 400 to 600 degrees Celsius, the carbon black reacts with adsorbed oxygen in the slurry mixture to generate carbon monoxide, which escapes and reduces the oxygen content of the alloy. The carbon black replenishes the carbon content in the alloy, ensuring the carbon content reaches the stoichiometric ratio. When the carbon black content is 0.04% to 0.06%, the free carbon content in the alloy after sintering is 0.04% to 0.08%, and the eta phase is absent. When the carbon black content is below 0.04%, the alloy is carbon-deficient, and the volume fraction of the eta phase after sintering is greater than 0.3%. When the carbon black content is above 0.06%, the alloy is carbon-rich, and the free carbon content after sintering is greater than 0.1%.

[0077] Regarding step 5, sintering: The sintering temperature is 1380°C to 1450°C. Cobalt's melting point is approximately 1495°C. At 1380°C to 1450°C, cobalt partially melts to form a liquid phase. Driven by capillary force, the liquid cobalt flows along the gaps between tungsten carbide particles, filling the pores. Ruthenium tungsten carbide compound powder, with a melting point above 1700°C, exists in solid form within the liquid cobalt at 1380°C to 1450°C. It is transported to the grain boundaries of the tungsten carbide grains along with the flow of the liquid cobalt. After holding at this temperature, the furnace cools, and the liquid cobalt solidifies to form a binder phase, while the ruthenium tungsten carbide compound particles remain at the grain boundaries of the tungsten carbide grains.

[0078] Regarding the Hall-Petch relationship: The average size d of tungsten carbide grains was measured using the cross-section method. A straight line was drawn along any direction on the polished metallographic sample, and the length of the cross-section where the line passes through the grain boundary was measured. The average length of the cross-sections of at least 500 grains was taken as Lavg. The average grain size d was calculated using the formula d = 1.56 multiplied by Lavg. The coefficient 1.56 is derived from the statistical correction factor for the grain size measurement using the cross-section method, which takes into account the correction for the grain cross-sectional shape deviating from the ideal spherical shape. Substituting the metallographic image measurement data from Example 1, Lavg equals 0.417 micrometers, and d equals 1.56 multiplied by 0.417 equals 0.650 micrometers, which is consistent with the grain size of 0.65 micrometers measured by scanning electron microscopy.

[0079] Regarding dispersion strengthening: Ruthenium-tungsten carbide compound particles exist as a dispersed phase at the grain boundaries of tungsten carbide grains, with an average particle size of 1 to 3 micrometers and a particle spacing of 1.5 to 3 micrometers. The dispersed phase strengthens the alloy in two ways: pinning grain boundary migration, hindering tungsten carbide grain growth during sintering; and sharing stress concentration at grain boundaries, improving the alloy's fracture toughness. In the comparative example, elemental ruthenium powder was directly added. During sintering, the Ru₂W₄C particles generated by the reaction of elemental ruthenium with tungsten carbide had an uneven size distribution, with some particles agglomerating to form clusters larger than 5 micrometers. Stress concentration at these clusters led to a decrease in the alloy's bending strength. After sintering, the residual Ru content in the comparative example was 4.2%, and the hardness fluctuated by 1.8 HRA. In Examples 1 to 3, the residual Ru content after sintering was all below 0.5%, and the hardness fluctuated by 0.4 to 0.5 HRA.

[0080] Regarding Zener pinning: Chromium carbide reacts with carbon in the alloy during sintering to form... , Precipitates at tungsten carbide grain boundaries, which pins the grain boundary migration. For particle sizes ranging from 0.1 to 0.3 micrometers and volume fractions from 0.3% to 0.6%, the corresponding Zener pinning pressure PZ is calculated using the formula PZ = 3f divided by 2r, where f is... The volume fraction, r is Particle radius. Substituting f = 0.005 and r = 0.1 micrometers, PZ = 3 multiplied by 0.005 divided by 2 multiplied by 0.1, which equals 0.075 MPa. This pinning pressure is comparable to the driving force for tungsten carbide grain growth, effectively suppressing abnormal grain growth.

[0081] The technical solution of the present invention will be described in detail below with reference to specific embodiments and comparative examples. All raw materials used in the embodiments are commercially available industrial-grade products. The purity of ruthenium powder is not less than 99.5%, the purity of tungsten carbide powder is not less than 99.8%, the purity of cobalt powder is not less than 99.5%, the purity of chromium carbide is not less than 99.0%, and the carbon black is acetylene black.

[0082] Example 1

[0083] 3000g of ruthenium powder and 3000g of ultrafine tungsten carbide powder were placed in a 5-liter horizontal ball mill, and 12000g of cemented carbide grinding balls were added. The mixture was ball-milled at 100 rpm for 3 hours to obtain a mixed powder. The average particle size of the ruthenium powder (FSSS) was 25 micrometers, and the average particle size of the ultrafine tungsten carbide powder (FSSS) was 0.65 micrometers.

[0084] The mixed powder was placed in a graphite boat and then placed in a vacuum sintering furnace. The furnace was evacuated to 5 Pa and heated to 1450°C at a rate of 4°C per minute, holding at this temperature for 2 hours. During this process, ruthenium powder and tungsten carbide powder underwent a solid-state reaction to produce a product with the chemical formula: Ruthenium tungsten carbide compounds were cooled to room temperature to obtain bulk solids.

[0085] The solid blocks are loaded into a ball mill, and cemented carbide grinding balls are added at a mass ratio of 2.5:1. The mixture is dry-milled for 3 hours and then passed through an 80-mesh sieve. The material passing through the sieve is ruthenium tungsten carbide compound powder with a particle size of 5 to 15 micrometers.

[0086] 2400g of ruthenium tungsten carbide compound powder, 212400g of tungsten carbide powder, 24000g of cobalt powder, 1200g of chromium carbide, and 120g of carbon black were mixed, and 72000g of anhydrous ethanol and 4800g of polyethylene glycol were added. The mixture was then wet-milled in an inclined ball mill with cemented carbide balls at a mass ratio of 5:1. The mill was tilted at 20 degrees and rotated at 35 revolutions per minute for 36 hours. During the wet milling process, the temperature was controlled to not exceed 10 degrees Celsius by using cooling water to obtain a mixed slurry.

[0087] The mixture slurry was dried using a centrifugal spray dryer with an atomizing disc speed of 16,000 rpm, an inlet temperature of 210 degrees Celsius, an outlet temperature of 95 degrees Celsius, and a feed rate of 6 liters per hour. The dried mixture was then molded on a hydraulic press at a pressure of 180 MPa for a holding time of 4 seconds to obtain a pressed blank.

[0088] The pressed billet was heated to 300°C in a vacuum sintering furnace at a rate of 2°C per minute, then to 400°C at a rate of 2°C per minute, held at 400°C for 1 hour, and then heated to 600°C at a rate of 8°C per minute and held for 15 minutes. After dewaxing, the billet was heated to 1420°C at a rate of 8°C per minute under a vacuum of 0.5 Pa and held for 1.5 hours. It was then cooled to room temperature in the furnace to obtain a reinforced ultrafine cemented carbide.

[0089] Example 2

[0090] 1500g of ruthenium powder and 1200g of ultrafine tungsten carbide powder were placed in a 5-liter horizontal ball mill, along with 5400g of cemented carbide grinding balls. The mixture was ball-milled at 90 rpm for 2 hours to obtain a mixed powder. The average particle size of the ruthenium powder (FSSS) was 15 micrometers, and the average particle size of the ultrafine tungsten carbide powder (FSSS) was 0.80 micrometers.

[0091] The mixed powder was placed in a graphite boat and then placed in a vacuum sintering furnace. The furnace was evacuated to 8 Pa and heated to 1380°C at a rate of 5°C per minute, holding at this temperature for 3 hours. During this process, ruthenium powder and tungsten carbide powder underwent a solid-state reaction to produce a product with the chemical formula […]. Ruthenium tungsten carbide compounds were cooled to room temperature to obtain bulk solids.

[0092] The solid blocks are loaded into a ball mill and dry-milled for 4 hours. The solids are then passed through an 80-mesh sieve. The material passing through the sieve is ruthenium tungsten carbide compound powder.

[0093] 1200g of ruthenium tungsten carbide compound powder, 228600g of tungsten carbide powder, 19200g of cobalt powder, 720g of chromium carbide, and 96g of carbon black were mixed, and 62400g of anhydrous ethanol and 3120g of polyethylene glycol were added. The mixture was then wet-milled in an inclined ball mill with a ball-to-material mass ratio of 4:1, an inclination angle of 15 degrees, a rotation speed of 30 rpm, and a wet-milling time of 28 hours. During the wet-milling process, the temperature was controlled to not exceed 10 degrees Celsius by cooling water to obtain a mixed slurry.

[0094] The mixture slurry is spray-dried at an inlet temperature of 200 degrees Celsius and an outlet temperature of 90 degrees Celsius. The dried mixture is then molded under a pressing pressure of 150 MPa for 3 seconds.

[0095] The compact was heated to 300°C at a rate of 1°C per minute, then to 400°C at a rate of 1°C per minute, held at 400°C for 0.5 hours, then to 600°C at a rate of 5°C per minute, and held for 10 minutes. After dewaxing, the compact was heated to 1380°C at a rate of 5°C per minute under a vacuum of 1 Pa, held for 2 hours, and then cooled to room temperature in the furnace to obtain a reinforced ultrafine cemented carbide.

[0096] Example 3

[0097] 4000g of ruthenium powder and 8000g of ultrafine tungsten carbide powder were placed in a 5-liter horizontal ball mill, along with 36000g of cemented carbide grinding balls. The mixture was ball-milled at 120 rpm for 4 hours to obtain a mixed powder. The average particle size of the ruthenium powder (FSSS) was 35 micrometers, and the average particle size of the ultrafine tungsten carbide powder (FSSS) was 0.50 micrometers.

[0098] The mixed powder was placed in a graphite boat and then placed in a vacuum sintering furnace. The furnace was evacuated to 3 Pa and heated to 1480°C at a rate of 3°C per minute, holding at this temperature for 1 hour. During this process, ruthenium powder and tungsten carbide powder underwent a solid-state reaction to produce a product with the chemical formula: Ruthenium tungsten carbide compounds were cooled to room temperature to obtain bulk solids.

[0099] The solid blocks are loaded into a ball mill and dry-milled for 3 hours. The solids are then passed through an 80-mesh sieve. The material passing through the sieve is ruthenium tungsten carbide compound powder.

[0100] 4800g of ruthenium tungsten carbide compound powder, 207600g of tungsten carbide powder, 28800g of cobalt powder, 1440g of chromium carbide, and 144g of carbon black were mixed, and 96000g of anhydrous ethanol and 5760g of polyethylene glycol were added. The mixture was then wet-milled in an inclined ball mill with a ball-to-material mass ratio of 6:1, an inclination angle of 25 degrees, a rotation speed of 40 rpm, and a wet-milling time of 40 hours. During the wet-milling process, the temperature was controlled to not exceed 10 degrees Celsius by cooling water to obtain a mixed slurry.

[0101] The mixture slurry is spray-dried at an inlet temperature of 220 degrees Celsius and an outlet temperature of 100 degrees Celsius. The dried mixture is then molded under a pressure of 200 MPa for 5 seconds.

[0102] The compact was heated to 300°C at a rate of 3°C per minute, then to 400°C at a rate of 3°C per minute, held at 400°C for 1.5 hours, then to 600°C at a rate of 10°C per minute and held for 20 minutes. After dewaxing, the compact was heated to 1450°C at a rate of 10°C per minute under a vacuum of 0.1 Pa and held for 1 hour. It was then cooled to room temperature in the furnace to obtain a reinforced ultrafine cemented carbide.

[0103] Comparative Example

[0104] 2400g of elemental ruthenium powder was directly mixed with 212400g of tungsten carbide powder, 24000g of cobalt powder, 1200g of chromium carbide, and 120g of carbon black. 72000g of anhydrous ethanol and 4800g of polyethylene glycol were added, and the mixture was wet-milled in an inclined ball mill with a ball-to-material mass ratio of 5:1. The wet milling time was 36 hours, and the temperature was controlled to not exceed 10 degrees Celsius during the wet milling process by using cooling water.

[0105] After wet milling, the slurry was spray-dried, pressed into shape, and then sintered at 1420 degrees Celsius for 1.5 hours under a vacuum of 0.5 Pa. The remaining process parameters were the same as in Example 1.

[0106] Table 1. Comparison of Process Parameters

[0107] Ruthenium powder particle size / μm 25 15 35 25 WC Powder Particle Size / μm 0.65 0.80 0.50 0.65 Ru:WC quality ratio 1:1 1:0.8 1:2 — Ball milling time / h 3 2 4 — Carbonization temperature / °C 1450 1380 1480 — Insulation time / h 2 3 1 — Ru-WC content / % 1.0 0.5 2.0 1.0 Co content / % 10.0 8.0 12.0 10.0 Cr3C2 content / % 0.5 0.3 0.6 0.5 Carbon black content / % 0.05 0.04 0.06 0.05 Wet grinding time / h 36 28 40 36 Sintering temperature / °C 1420 1380 1450 1420 Ru addition method Pre-preparation Pre-preparation Pre-preparation Add directly

[0108] Table 2 Product Performance Comparison Table

[0109] Residual Ru content / % <0.5 <0.5 <0.5 4.2 XRDRu characteristic peaks Not detected Not detected Not detected Detected WC grain size / μm 0.65 0.72 0.58 0.70 Hardness fluctuation / HRA 0.4 0.5 0.4 1.8 Rockwell hardness / HRA 92.0 91.5 92.5 91.2 Flexural strength / MPa 3900 3800 3850 3400 fracture toughness KiC 10.1 9.8 9.5 8.2 Relative density / % 99.5 99.2 99.6 98.8

[0110] Obviously, those skilled in the art can make various modifications and variations to this application without departing from the scope of this application. Therefore, if such modifications and variations fall within the scope of the claims of this application and their equivalents, this application also intends to include such modifications and variations.

Claims

1. A method for preparing reinforced ultrafine cemented carbide, characterized in that, Includes the following steps: Ruthenium powder and ultrafine tungsten carbide powder are loaded into a ball mill, and cemented carbide grinding balls are added. The mass ratio of the balls to the powder is 2:1 to 3:

1. The mixture is ball-milled at a speed of 80 to 120 rpm for 2 to 5 hours to obtain a mixed powder. The mixed powder is placed in a graphite boat and then placed in a vacuum sintering furnace. The furnace is evacuated to a vacuum level not exceeding 10 Pa, and the temperature is increased at a rate of 3 to 5 degrees Celsius per minute to 1380 to 1480 degrees Celsius. The temperature is maintained for 1 to 3 hours, during which the ruthenium powder and tungsten carbide powder undergo a solid-phase reaction to produce a product with the chemical formula […]. Ruthenium tungsten carbide compounds are cooled to below 80 degrees Celsius to obtain bulk solids; The solid blocks are loaded into a ball mill, and cemented carbide grinding balls are added. The ball-to-material mass ratio is 2:1 to 3:

1. The mixture is dry-milled for 2 to 4 hours and then passed through a 60-mesh to 100-mesh sieve. The material passing through the sieve is ruthenium tungsten carbide compound powder. By mass percentage, 0.5 to 2 parts of ruthenium tungsten carbide compound powder, 86 to 91 parts of tungsten carbide powder, 8 to 12 parts of cobalt powder, and 0.3 to 0.6 parts of chromium carbide are mixed, and anhydrous ethanol is added for wet milling. The amount of anhydrous ethanol added is 25% to 35% of the total mass of the mixture. The wet milling is carried out in an inclined ball mill, and the grinding balls are cemented carbide balls with a ball-to-material mass ratio of 4:1 to 6:

1. The wet milling time is 28 to 40 hours. During the wet milling process, the temperature is controlled not to exceed 10 degrees Celsius by cooling water to obtain a mixed slurry. The mixed slurry is spray-dried and pressed into shape, and then sintered at 1380°C to 1450°C for 1 to 2 hours under a vacuum of no more than 1 Pa to obtain a reinforced ultrafine cemented carbide.

2. The method for preparing a reinforced ultrafine cemented carbide as described in claim 1, characterized in that: The specific process of ball milling and mixing described in step 1 is as follows: Ruthenium powder with an average FSSS particle size of 15 to 35 micrometers and ultrafine tungsten carbide powder with an average FSSS particle size of 0.5 to 0.8 micrometers were loaded into a 5-liter horizontal ball mill. The mass ratio of ruthenium powder to ultrafine tungsten carbide powder was 1:0.8 to 2. Carbide grinding balls were added, with a mass of 2 to 3 times the total mass of ruthenium powder and ultrafine tungsten carbide powder. The mixture was ball-milled at a speed of 90 to 110 rpm for 3 to 4 hours. During ball milling, larger ruthenium powder particles roll and adhere to the surface of smaller ultrafine tungsten carbide powder particles, forming a composite powder in which ruthenium powder is coated with ultrafine tungsten carbide powder. The contact area between ruthenium powder and ultrafine tungsten carbide powder in this composite powder is 10 times larger than that in simple mixing. After ball milling is completed, all the powder in the ball mill is discharged and passed through a 40-mesh sieve to remove the grinding balls and the material on the sieve. The material that passes through the sieve is the mixed powder.

3. The method for preparing a reinforced ultrafine cemented carbide as described in claim 2, characterized in that: The specific process of vacuum carbonization described in step 2 is as follows: The mixed powder is loaded into a graphite boat with a filling height of 30 mm to 50 mm. The graphite boat is placed in the constant temperature zone of the vacuum sintering furnace. After closing the furnace door, the vacuum system is started and the vacuum is evacuated to below 5 Pa. The temperature was increased from room temperature to 1400 to 1480 degrees Celsius at a rate of 4 to 5 degrees Celsius per minute, while the vacuum level was maintained below 10 Pa during the heating process. After reaching the set temperature, maintain the temperature for 2 to 3 hours, and keep the vacuum level below 5 Pa during the heat preservation process; After the heat preservation is completed, the heating power is turned off, and the furnace is cooled to below 80 degrees Celsius. Then the graphite boat is removed from the furnace to obtain a blocky solid. X-ray diffraction was performed on the bulk solid sample. The scanning angle 2θ ranged from 20 to 90 degrees, the step size was 0.02 degrees, and the scanning speed was 2 degrees per minute. It was confirmed that the characteristic diffraction peaks of ruthenium at 2θ equal to 38.4 degrees, 44.0 degrees, and 64.6 degrees disappeared, and the characteristic diffraction peaks of ruthenium tungsten carbide compounds appeared at 2θ equal to 36.2 degrees, 42.5 degrees, and 61.8 degrees.

4. The method for preparing a reinforced ultrafine cemented carbide as described in claim 1, characterized in that: The specific process of dry grinding and crushing described in step 3 is as follows: The solid blocks are loaded into a ball mill, and hard alloy grinding balls with a diameter of 5 mm to 10 mm are added. The ball-to-material mass ratio is 2.5:1 to 3:

1. The balls are then dry-ground at a speed of 60 to 80 rpm for 3 to 4 hours. The powder after dry grinding is passed through a 60-mesh sieve and an 80-mesh sieve in sequence. When passing through the 60-mesh sieve, the mass fraction of the material on the sieve is 5% to 10%, and it is returned to the ball mill for further dry grinding. The material passing through the 60-mesh sieve is then passed through the 80-mesh sieve. When passing through the 80-mesh sieve, the mass fraction of the material on the sieve is 15% to 25%, and it is returned to the ball mill for further dry grinding. The material passing through an 80-mesh sieve is ruthenium tungsten carbide compound powder, with a particle size of 5 to 15 micrometers. The ruthenium tungsten carbide compound powder is placed in a sealed container and stored under nitrogen protection for no more than 72 hours.

5. The method for preparing a reinforced ultrafine cemented carbide as described in claim 1, characterized in that: The specific process of wet grinding of ingredients in step 4 is as follows: By weight percentage, 0.8 to 1.5 parts of ruthenium tungsten carbide compound powder, 87 to 90 parts of tungsten carbide powder, 9 to 11 parts of cobalt powder, 0.4 to 0.6 parts of chromium carbide, and 0.04 to 0.06 parts of carbon black are loaded into an inclined ball mill. Add anhydrous ethanol at a concentration of 28% to 32% of the total mass of the mixture, and then add polyethylene glycol (PEG) with a molecular weight of 4000 at a concentration of 1.2% to 1.8% of the total mass of the mixture. Add cemented carbide grinding balls with a diameter of 3 mm to 6 mm and a ball-to-material mass ratio of 5:1 to 6:

1. During the wet grinding process, cooling water is introduced through the jacket of the ball mill. The inlet temperature of the cooling water is 5 to 8 degrees Celsius, and the outlet temperature does not exceed 12 degrees Celsius. The temperature of the slurry inside the ball mill is controlled to be no higher than 10 degrees Celsius. After wet grinding, the slurry is discharged from the ball mill and passed through a 200-mesh sieve to remove the grinding balls. The material passing through the sieve is the mixed slurry.

6. The method for preparing a reinforced ultrafine cemented carbide as described in claim 5, wherein the carbon black is acetylene black, the particle size of the carbon black is 30 nanometers to 50 nanometers, and the specific surface area is 60 square meters per gram to 80 square meters per gram; During the wet milling process, carbon black is uniformly dispersed in the slurry mixture. In the early stage of sintering, it reacts with excess oxygen in the slurry mixture to generate carbon monoxide, which then escapes. Carbon black is used to supplement the carbon content in the alloy, so that the carbon content of the alloy reaches the stoichiometric ratio. After sintering, the free carbon content in the alloy is 0.04% to 0.08%, and there is no eta phase in the alloy.

7. The method for preparing a reinforced ultrafine cemented carbide as described in claim 5, characterized in that: The specific process of spray drying and pressing in step 5 is as follows: The mixed slurry is fed into a centrifugal spray dryer with an atomizing disc speed of 15,000 to 18,000 rpm, an inlet temperature of 200 to 220 degrees Celsius, an outlet temperature of 90 to 100 degrees Celsius, and a feed rate of 5 to 8 liters per hour. The moisture content of the dried mixture is 0.1% to 0.3%, the Hall flowability is 30 seconds per 25 square centimeters to 45 seconds per 25 square centimeters, and the loose density is 2.8 g per cubic centimeter to 3.2 g per cubic centimeter. The dried mixture is loaded into a mold and molded on a hydraulic press at a pressing pressure of 160MPa to 200MPa and a holding time of 3 to 5 seconds to obtain a pressed blank. The density of the pressed blank is 52% to 55% of the theoretical density, and the dimensional accuracy of the pressed blank is ±0.5% of the nominal size.

8. The method for preparing a reinforced ultrafine cemented carbide as described in claim 7, characterized in that: Step 5, prior to sintering, also includes a dewaxing step: The pressed blank is placed into a graphite boat in the sintering furnace, and the vacuum is drawn to below 1 Pa. The temperature is then increased from room temperature to 300 degrees Celsius at a rate of 1 to 3 degrees Celsius per minute. Starting from 300 degrees Celsius, polyethylene glycol begins to decompose and volatilize. The temperature is then increased at a rate of 1 to 3 degrees Celsius per minute to 400 degrees Celsius, and held at 400 degrees Celsius for 0.5 to 1.5 hours. Increase the temperature from 400 degrees Celsius to 600 degrees Celsius at a rate of 5 to 10 degrees Celsius per minute, and hold at 600 degrees Celsius for 10 to 20 minutes. During the dewaxing process, the vacuum level inside the furnace is maintained below 1 Pa, and after the dewaxing is completed, the vacuum level returns to below 0.1 Pa. The volatiles generated during dewaxing are collected by condensation and then treated uniformly.

9. The method for preparing a reinforced ultrafine cemented carbide as described in claim 1, characterized in that: The specific sintering process described in step 5 is as follows: The dewaxed compact is heated in a vacuum sintering furnace at a rate of 5 to 10 degrees Celsius per minute to 1400 to 1450 degrees Celsius per minute. After reaching the set temperature, maintain the temperature for 1 to 2 hours, keeping the vacuum level below 0.1 Pa during the maintenance process; During the sintering process, cobalt powder melts to form liquid cobalt, which flows along the gaps between tungsten carbide particles, filling the pores between the particles.

10. The method for preparing a reinforced ultrafine cemented carbide as described in claim 1, characterized in that: The reinforced ultrafine cemented carbide has the following microstructure and property characteristics: The average size of tungsten carbide grains is 0.5 to 0.8 micrometers. The cross-sectional length Lavg of no less than 500 grains is measured using the cross-sectional method. The average grain size d is calculated by the formula d = 1.56 multiplied by Lavg. Ruthenium tungsten carbide compound particles exist as a dispersed phase at the grain boundaries of tungsten carbide grains, with an average particle size of 1 to 3 micrometers and a particle spacing of 1.5 to 3 micrometers. The alloy has a Rockwell hardness (HRA) of 91.5 to 92.5, a bending strength of 3800 MPa to 4200 MPa, and a fracture toughness (KiC) of 9.5 MPa·m1 / 2 to 11.0 MPa·m1 / 2. The reinforced ultrafine cemented carbide is used for machining carbon fiber reinforced composite materials, nickel-based superalloys, or hardened steel.